2019
DOI: 10.3390/nano9091205
|View full text |Cite
|
Sign up to set email alerts
|

Efficient, Stable, and Low-Cost PbS Quantum Dot Solar Cells with Cr–Ag Electrodes

Abstract: PbS quantum dots (QDs) are a promising nanostructured material for solar cells. However, limited works have been done to explore the active layer thickness, layer deposition techniques, stability improvement, and cost reduction for PbS QD solar cells. We address those issues of device fabrication herein and suggest their possible solutions. In our work, to get the maximum current density from a PbS QD solar cell, we estimated the optimized active layer thickness using Matlab simulation. After that, we fabricat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Micromachines 2020, 11, 817 3 of 9 concentration caused a multilayered QD film. [30,31] All electrochemical measurements were performed with a three-electrode configuration. As-prepared quantum dots on ITOs were utilized as working electrodes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Micromachines 2020, 11, 817 3 of 9 concentration caused a multilayered QD film. [30,31] All electrochemical measurements were performed with a three-electrode configuration. As-prepared quantum dots on ITOs were utilized as working electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…By several tests, we came to know that the controlled concentration of “~10 7 particles/µL” asked two times (or less than) drop-deposition of 10 µL QD solution onto 2 cm 2 area of ITO for making a monolayered QD layer; more than 20 µL dropping and drying under current QD concentration caused a multilayered QD film. [ 30 , 31 ] All electrochemical measurements were performed with a three-electrode configuration. As-prepared quantum dots on ITOs were utilized as working electrodes.…”
Section: Methodsmentioning
confidence: 99%
“…The ability of organic materials to tune their bandgap energy revealed a new field of practices for niche applications of building-integrated photovoltaics (PVs), such as self-powered greenhouses and powered windows, known as semi-transparent organic photovoltaics (ST-OPVs). Despite the fact that ST-OPVs have not yet been commercialized, the trade-off between device efficiency and average visible transparency (AVT) remains a challenge, and a number of researchers have assigned their research to increasing the efficiency to a commercial standard and optimizing (AVT) as well [17][18][19][20]. A review of the literature showed that there were useful reviews on ternary systems for bulk heterojunction structures [21][22][23][24][25][26][27][28][29][30], as well as several interesting reviews on the progress of semi-transparent organic solar cells, from materials to device performance [31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%